2018
DOI: 10.1007/s10803-018-3504-2
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Effectiveness of a Peer-Mediated Model of the PEERS Curriculum: A Pilot Randomized Control Trial

Abstract: This study compared immediate and 4-month outcomes among adolescents with autism spectrum disorder randomly assigned to the PEERS curriculum (n = 10), a peer mediated PEERS curriculum (n = 12), or a delayed treatment control group (n = 12). Findings suggest a modest advantage in social skills knowledge and social functioning for participants in the peer-mediated PEERS curriculum relative to Traditional PEERS, and gains in social skills knowledge, social functioning, and reductions in loneliness were maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 33 publications
0
70
0
Order By: Relevance
“…A search of the current literature evaluating SSGTs for adolescents via randomized controlled trials (RCTs), identified a number of design and intervention limitations. Consistent design limitations included small sample sizes (9,(27)(28)(29)(30)(31), failing to employ blinded or external observer-report measurement of dependent variables (17,20,27,29,30,(32)(33)(34)(35), failing to describe the randomization processes (27, 29-31, 33, 34) or employ allocation concealment (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), limited application of intent-to-treat data analysis (17,(27)(28)(29)(30)(32)(33)(34)(35), a lack of clarity in regard to compliance with the Consolidated Standards of Reporting Trials (CONSORT) statement (20,27,29,30,35,36), and limited examples of mixed methods studies integrating quantitative and qualitative data collection methods and analysis in understanding the outcomes of interventions…”
Section: Social Skills Group Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…A search of the current literature evaluating SSGTs for adolescents via randomized controlled trials (RCTs), identified a number of design and intervention limitations. Consistent design limitations included small sample sizes (9,(27)(28)(29)(30)(31), failing to employ blinded or external observer-report measurement of dependent variables (17,20,27,29,30,(32)(33)(34)(35), failing to describe the randomization processes (27, 29-31, 33, 34) or employ allocation concealment (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), limited application of intent-to-treat data analysis (17,(27)(28)(29)(30)(32)(33)(34)(35), a lack of clarity in regard to compliance with the Consolidated Standards of Reporting Trials (CONSORT) statement (20,27,29,30,35,36), and limited examples of mixed methods studies integrating quantitative and qualitative data collection methods and analysis in understanding the outcomes of interventions…”
Section: Social Skills Group Trainingmentioning
confidence: 99%
“…A range of identified intervention shortcomings included limited consideration or incorporation of adolescents' personal goals (20, 27-31, 33, 34, 36), outcomes largely measured by parent proxy report (17,28,29,31,32,35,36), inadequate tailoring of interventions to individual activity preferences (20,29,30,(33)(34)(35)(36), failing to consider the relationship between intervention dosage (that is the number of sessions) and outcomes (20,(27)(28)(29)(30)(31)(33)(34)(35)(36), the absence of cost analysis (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and limited reporting of adverse events during the intervention period (20, 27-30, 32-34, 36) (Additional file 1). While comparison groups varied considerably, most examined the efficacy of SSGT interventions relative to usual care waitlist control groups, with limited description of what interventions and therapies were received by comparison groups.…”
Section: (Additional Files 1 and 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…A search of the current literature evaluating SSGTs for adolescents via randomized controlled trials (RCTs), identified a number of design and intervention limitations. Consistent design limitations included small sample sizes (9,(27)(28)(29)(30)(31), failing to employ blinded or external observer-report measurement of dependent variables (17,20,27,29,30,(32)(33)(34)(35), failing to describe the randomization processes (27, 29-31, 33, 34) or employ allocation concealment (17,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), limited application of intent-to-treat data analysis (17,(27)(28)(29)(30)(32)(33)(34)(35), a lack of clarity in regard to compliance with the Consolidated Standards of Reporting Trials (CONSORT) statement (20,27,29,30,35,36), and limited examples of mixed methods studies integrating quantitative and qualitative data collection methods and analysis in understanding the outcomes of interventions (17) (Additional fil...…”
Section: Social Skills Group Trainingmentioning
confidence: 99%